PIK3CA mutational status in tissue and plasma as a prognostic biomarker in HR+/HER2− breast cancer - Eduardo Terán; Rebeca Lozano; César A. Rodríguez; Mar Abad; Luis Figuero; José Antonio Muñoz; Belén Cigarral; Aline Rodrígues; Magdalena Sancho; M. Asunción Gómez; Daniel Morchón; Juan Carlos Montero; et al. (Cancer Medicine)
Abstract Introduction Hotspots (HS) mutations in the PIK3CA gene may lead to poorer oncological outcomes and endocrine resistance in advanced breast cancer (BC), but their prognostic role in early‐stage disease remains controversial. The overall agreement within plasma and tissue methods has not been well explored. Our aim was to correlate tissue and plasma approaches and to analyze the prognostic impact of PIK3CA mutations (PIK3CAm) in HR+/HER2− BC. Methods A retrospective and unicentric analysis of PIK3CA mutational status in tissue and plasma samples by Cobas®PIK3CA Mutation Kit in patients with HR+/HER2− BC. Results We analyzed 225 samples from 161 patients with luminal BC. PIK3CA mutations were identified in 62 patients (38.5%), of which 39.6% were found in tissue and 11.8% in plasma. In advanced disease, plasma and tissue correlation rate was performed in 64 cases, with an overall agreement of 70.3%. Eighty patients were treated with CDK4/6 inhibitors + endocrine therapy. We observed a moderately worse progression‐free survival (PFS) in PIK3CAm versus wild‐type (WT) (24 m vs. 30 m; HR = 1.39, p = 0.26). A subanalysis was carried out based on exons 9 and 20, which showed a statistically poorer PFS in PIK3CAm exon 9 versus 20 population (9.7 m vs. 30.3 m; HR = 2.84; p = 0.024). Furthermore, detection of PIK3CAm in plasma was linked to a worse PFS vs PIK3CAm detection just in tissue (12.4 vs. 29.3; HR = 2.4; p = 0.08). Conclusions Our findings suggest the PIK3CA evaluation in tissue as the diagnostic method of choice, however, additional investigations are required to improve the role of liquid biopsy in the PIK3CA assessment. PIK3CAm show worse outcomes in advanced luminal BC, especially in exon 9 mutation carriers, despite visceral involvement, prior exposure to endocrine therapy or detection of PIK3CAm in plasma, with an unclear prognosis in early‐stage disease. Nonetheless, this should be validated in a prospective cohort study.